Exploring The Strategies Of Nurses in Giving Health Teachings Among Diabetes Mellitus (DM) Patients - Soriano, Ralph Jasper; Adante, Nazel D; M. Agbuya, Jhezel Giana; B. Beñales, Lee Ann; Dela Cruz, Izzy R.; Gatus, Jon Christoper A.; N. Salaya, Amanda Jhulia Mari; Aggari, Michael I.; Marced, Joel John Dela; Flores, Annabelle; Salcedo, Trinidad J.; Guevarra, Cecile F.; Lopez, Mary Ann; B. Jecino, Liza May; E. Abonalla, Arby James (MALATA SAINS INDONESIA, 2024)
Introduction: Effective health teaching has been shown to have a major impact on patients' behavior and disease management. The strategies used by nurses to educate patients with diabetes mellitus, with an emphasis on the impact of the nurses' experiences in providing health teaching on diabetes management, were explored by the researchers. Objective: The goal of this study is to provide the best strategy based on insights and experiences of the nurses in giving health teachings for the management of diabetes mellitus. Method: Phenomenological approach using Colaizzi's descriptive method was utilized and conducted through verbal interview. Seven (7) registered nurses who had prior experience in educating patients with diabetes mellitus from a well-known public health institution located in Quezon City participated in data collection. An open-ended unstructured subjective type questionnaire that was prepared by the researchers was used to gather the data. Result: The significant findings of this study revealed nine (9) key themes in health teaching, covering its importance, strategies, challenges, addressing challenges, adapting strategies to patient needs, family involvement, impact of family involvement, strategies to persuade colleagues to adopt health teaching methods, and effective teaching strategies that the nurses employ in delivering health education to diabetes mellitus patients. The results showed that challenges like beliefs, socioeconomic status, and psychological problems could arise. Conclusion: This study concentrated on the utmost importance of nurses' experiences in helping to recognize and comprehend various strategies in health teaching through which they can help patients with diabetes mellitus find appropriate self-management techniques, thereby enhancing the quality of patient care.